(untitled) (Medico Legal Update, 2020)
The speedy progress of trade in Global Health Services is limited by legal barrier. Advances in technology and cross-border movement of people and health services form legal ambiguities and uncertainties for businesses and consumers involved in transnational medical malpractice disputes. This requires for a uniform means of redress which is more flexible and predictable as compared to litigation in a court room. Therefore, the voluntary, flexible and legally binding nature of arbitration agreements across jurisdictions make this form of dispute resolution efficient and adaptive to changes in the health services industry. With careful making of an approach that accounts for arbitration cost, reasonable recovery amount and complementary mechanisms such as no-fault compensation, international arbitration of medical malpractice disputes will change the legal risks borne by businesses and consumers more fairly and efficiently. This paper argue that most medical disputes are better resolved by alternative dispute resolution mechanisms which will contribute in improving patient safety by encouraging candid and comprehensive reporting of risks. It also argues that medical disputes and patient safety needs to be viewed through a new lens, namely patient autonomy. It discusses the scope of India flourishing in the field of Medical Tourism and also the challenges faced by the foreign patients and the scope of Arbitration in amicably resolving the medical disputes in a cost effective and in a swift manner.